Molecular characterisation of Acinetobacter baumannii isolates from bloodstream infections in a tertiary-level hospital in South Africa - Lowe, Michelle; Singh-Moodley, Ashika; Ismail, Husna; Thomas, Teena; Chibabhai, Vindana; Nana, Trusha; Lowman, Warren; Ismail, Arshad; Chan, Wai Yin; Perovic, Olga (Frontiers in Microbiology, 2022)
Acinetobacter baumannii is an opportunistic pathogen and causes various infections in patients. This study aimed to describe the clinical, epidemiological and molecular characteristics of A. baumannii isolated from BCs in patients at a tertiary-level hospital in South Africa. Ninety-six isolates from bloodstream infections were collected. Clinical characteristics of patients were recorded from patient files. Organism identification and AST was performed using automated systems. PCR screening for the mcr-1 to mcr-5 genes was done. To infer genetic relatedness, a dendrogram was constructed using MALDI-TOF MS. All colistin-resistant isolates (n=9) were selected for WGS. The patients were divided into three groups, infants (<1 year; n=54), paediatrics (1-18 years; n=6) and adults (≥19 years; n=36) with a median age of 13 days, 1 year and 41 years respectively. Of the 96 A. baumannii bacteraemia cases, 96.9% (93/96) were healthcare-associated. The crude mortality rate at 30 days was 52.2% (48/92). The majority of the isolates were MDR. All isolates were PCR-negative for the mcr-1 to mcr-5 genes. The majority of the isolates belonged to cluster 1 (62/96) according to the MALDI-TOF MS dendrogram. Colistin resistance was confirmed in nine A. baumannii isolates (9.4%). The colistin-resistant isolates belonged to sequence type (ST) 1 (5/6) and ST2 (1/6). The majority of ST1 isolates showed low SNP diversity (≤4 SNPs). All the colistin-resistant isolates were resistant to carbapenems, exhibited an XDR phenotype and harboured the blaOXA-23 gene. The blaNDM gene was only detected in ST1 colistin-resistant isolates (n=5). The lpsB gene was detected in all colistin-resistant isolates as well as various efflux pump genes belonging to the RND, the MFS and the SMR families. The lipooligosaccharide OCL1 was detected in all colistin-resistant ST1 and ST2 isolates and the capsular polysaccharide KL3 and KL17 were detected in ST2 and ST1 respectively. This study demonstrated a 9.4% prevalence of colistin-resistant ST1 and ST2 A. baumannii in BC isolates. The detection of the lpsB gene indicates a potential threat and requires close prospective monitoring.